A Review of Cloud-Based ERP Systems in SMEs - Jaffa, Syammon; Salim , Siti Aisyah (International Journal of Integrated Engineering, 2020)
The adoption of Enterprise Resource Planning (ERP) system in small and medium enterprises (SMEs) could offer significant benefits in terms of managing the resources and support business function. However, the traditional ERP systems are quite expensive and have complex procedures for the adoption especially for SMEs. With the introduction of cloud-based ERP systems that have similar functionalities with traditional ERP, SMEs are now able to adopt this system. However, the adoption of cloud ERP remains low and question arise on how to encourage SMEs to adopt this system. Drawing from management and Information Systems literature, this study proposes and conceptual framework for cloud ERP adoption among SMEs. Using archival analysis approach and technology-push and demand-pull as the theoretical background, this research has come out with six main themes namely: firm qualities, internal pressure, external pressure, technology features, organizational readiness and external support. This paper will give significant benefits to ERP vendors to understand their potential buyer’s behaviour towards the adoption of cloud ERP.